ERGONOMICS INVESTIGATION OF MUSCULOSKELETAL DISORDER AMONG THE WORKFORCE OF WASTE MANAGEMENT INDUSTRY IN NIGERIA - Adekunle I. MUSA; Abiodun A. YUSSOUFF; Nurudeen A. RAJI; Temitayo S. OGEDENGBE; Rasheed O. SAHEED (Transactions of the VŠB: Technical University of Ostrava, Safety Engineering Series, 2017)
The objective of this study is to undertake an Ergonomic Scrutiny of Desecrate Management Industry. Ten (10) employees of the parking and collection department of Kim Waste Management Authority (KWMA) were selected. Their activities were video and recorded while working and their different postures were analyzed using Rapid Entire Body Assessment (REBA) and Rapid Upper Limb Assessment (RULA). Result showed that 10% were at medium risk; 40% were at high risk and 50% were at very high risk for the workers in KWMA. It as discovered that workers are subjected to Musculoskeletal Disorder (MSDs) as a result of the postures adopted during the work process.